Do salinity, total nitrogen and phosphorus variation induce oxidative stress in emergent macrophytes along a tropical estuary? - Santini, Rachel [UNESP]; Vantini Checchio, Mirela [UNESP]; Correia Nunes, Laís Samira; Lupino Gratão, Priscila [UNESP]; Monteiro Camargo, Antonio Fernando [UNESP] (Springer Nature, 2024)
Aquatic plants suffer stress caused by abiotic and biotic variables. In estuaries, salinity is one of the main abiotic factors responsible for stress. This study aimed to evaluate oxidative stress in two species of aquatic macrophytes (Crinum americanum and Spartina alterniflora) that are common in Brazilian tropical estuaries. We measured reactive oxygen species (hydrogen peroxide and malondialdehyde) and total nitrogen (TN) and total phosphorus (TP) in the aboveground and belowground biomass of the species. In addition, we measured salinity, TN, and TP content in the sediment. Statistical tests included t test and the analysis of variance (ANOVA) followed by the Tukey’s test. Our results showed that the greatest oxidative stress, in both species, occurred in areas of the estuary with lower salinity. For C. americanum, limitation by TN and TP content in the sediment is the main cause of oxidative stress. For S. alterniflora, the presence of C. americanum and the allelopathic compounds released by it seem to be the major cause of oxidative stress. Salinity did not induce oxidative stress in C. americanum and S. alterniflora in the estuary; however, the difference in TP and TN contents in the sediment played an important role in their responses to oxidative stress.
Keywords: Abiotic stress; Crinum americanum; Salt stress; Spartina alterniflora